Pengaruh Kemiringan Saluran Terhadap Fenomena Flooding Dengan Gangguan Pada Aliran Udara–Air Dan Udara–Minyak Tanah - Hendri Candra Mayana (Politeknik Negeri Padang, 2018)
Some equipments which are used in petroleum industries, chemical industries, steam power-plants and nuclear reactors must avoid the flooding phenomena in order to work at optimal condition. The purpose of this research is to investigate the effects of inclination and obstacle on flooding onset at counter-current air-water and air-kerosene flows with porous inlet and sharp outlet. The model of obstacle was conformed to industrial application i.e .pipe joining or pipe scaling. Experimen ts were conducted in a plexyglass pipe of 25.4 mm diameter and 2500 mm length of test section at annular flow pattern. The variation of inclination of ducts are 90o, 80o and 60o. The geometry of the obstacle is a ring with rectangular cross sectional which is installed with a distance 600 mm or 1200 mm from the inlet. The result of the research indicated that the effects of inclination and obstacle of ducts are significant toward flooding onset. Flooding phenomena was indicated with drastic increase of pressure gradient above the liquid inlet. Flooding phenomena happened earlier of larger inclination of the ducts and nearer obstacle of the inlet. This phenomena also early happened at kerosene which have higher viscosity and lower surface tension than water